ANALISIS BIOEKONOMI PENGELOLAAN SUMBERDAYA IKAN PELAGIS DI KABUPATEN ACEH UTARA - Dara Malahayati; Indra Indra; Muhammad Nasir (Jurnal Agrisep, 2016)
North Aceh Regency is one of regency in Aceh Province that have pelagical fish. This research aims were to knows the actual function model of sustainable and pelagic fish right in fishing effort. To estimate and analyze value biomass, catch and optimal effort. To analyze efficiency of fisheries. Research method was survei method. Data collected consist of primary data and secondary data. Data analysis method used times seriesand bioeconomic methode- Gordon Schaefer Model. Results shows that the actual function model of sustainable and pelagic fish in North Aceh regency showed trajectory continues to rise. The estimated value and value analysis biomass, the catch and effort by using MDR 15% obtained optimal biomass values (x) = 33 327.96 tonnes, optimal production (h) = 16 085.26 tonnes, and optimal effort (E) = 89 190.00. The optimal value by 6.84% RDR obtained optimal biomass (x) = 32 452.00 tonnes, optimal production (h) = 16 388.00 tonnes, optimal effort (E) = 93 320.00 trip. By using the value of a smaller discount rate (RDR 6.84%), the obtained optimal value of the biomass is relatively higher and relatively lower input than calculations using 15% MDR. Capture fisheries management in the North Aceh Regency increasingly inefficient and therefore in order to reduce the additional input.